2022
DOI: 10.1002/jtr.2536
|View full text |Cite
|
Sign up to set email alerts
|

Is local food consumption memorable? Exploration of a multidimensional measurement scale to explain tourists' memorable local food consumption experiences

Abstract: Recent trends in local food consumption have stimulated research interest in what makes tourists' local food experiences memorable. Despite previous attempts at investigating this phenomenon, theoretical gaps exist regarding its dimensional structure and the measurement of memorable local food consumption experiences (MLFCEs). Therefore, this study sought to examine the underlying dimensionality and measurement of MLFCEs. An eight‐factor structure for MLFCEs was generated. The overall construct satisfied a ser… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(3 citation statements)
references
References 93 publications
0
3
0
Order By: Relevance
“…A study on tourists' slow food experiences revealed that slow food experiences have a positive impact on tourists' quality of life [ 23 ]. Badu-Baiden and Kim [ 46 ] developed the memorable local food consumption experiences (MLFCEs) scale and verified through structural equation modeling that the scale has strong explanatory power concerning local food attitudes, subjective well-being, and destination loyalty.…”
Section: Literature Review and Theoretical Hypothesismentioning
confidence: 99%
See 1 more Smart Citation
“…A study on tourists' slow food experiences revealed that slow food experiences have a positive impact on tourists' quality of life [ 23 ]. Badu-Baiden and Kim [ 46 ] developed the memorable local food consumption experiences (MLFCEs) scale and verified through structural equation modeling that the scale has strong explanatory power concerning local food attitudes, subjective well-being, and destination loyalty.…”
Section: Literature Review and Theoretical Hypothesismentioning
confidence: 99%
“…Lifestyles associated with food have a positive impact on attitudes and contribute to satisfaction with experiences and overall life satisfaction [ 44 , 45 ]. Tourists' attitudes towards local food can explain the mechanisms behind their affective, psychological, and subjective well-being [ 7 , 35 , 46 ]. However, there is a lack of explicit and systematic research on the mechanisms by which tourists' attitudes and satisfaction are affected by the food tourism experience on tourists' subjective well-being.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, Rajamangsa Culinary also has an essential role as a supporting destination for Sojiwan Temple in Kebondalem Kidul Cultural Tourism Village. The "memorable tourism experience" approach can effectively increase visitor attraction and positive experiences at this location (Badu-Baiden & Kim, 2022;. The concept of Rajamangsa cultural culinary tourism was born because several factors have raised concerns regarding the sustainability of tourism in this location.…”
Section: Introductionmentioning
confidence: 99%